Social support of dual-physician families with multiple children aged zero to five years - Morabe, Maria Cristina S.; Valdes, Judith Adrienne F.
Childcare is a universal concern among families, especially when both parents are working on demanding careers. This research described the childcare arrangements of dual-physician families with multiple children aged zero to five years, as well as the social support that these families receive pertaining to childcare. Fifteen Filipino dualphysician couples participated through a pre-interview survey form, and a semistructured interview to detail their current childcare arrangements. The survey looked into the daily routines of the children, the persons in charge of these activities, and the identified primary caregiver of the children. Participants also identified the kinds and sources of social support that they receive in terms of childcare. Findings showed that for the majority of these dual physician families, the mothers were considered the primary caregivers of their children although they relied on paid live-in nannies to assist them in the actual caregiving tasks. The extended family system, especially the maternal grandparents, provided the most significant social support in terms of childcare. There was little reliance on formal support systems like public daycare centers. It is recommended that policymakers consider the provision of daycare facilities with certified caregivers and accredited facilities, and operating at longer hours, to provide safe, secure, and intellectually stimulating environments to support dual income and dual- career families with multiple young children who are likely to share the same concerns about childcare.